Konsep Akad Murabahah Pada Perbankan Syariah (Analisa Kritis Terhadap Aplikasi Konsep Akad Murabahah Di Indonesia Dan Malaysia) - Bagya Agung Prabowo (Jurnal Hukum IUS QUIA IUSTUM, 2009)
There are significant differences in the practice of murabahah scheme between Indonesia and Malaysia. The most distinct feature between them is in the adoption of bai’ ail-inah in Malaysia wich is not applicable in Indonesia. National Shariah Council of Indonesia condemns such contract as fraudelent, and hence is fobiddento apply. Here, the contract is designated to be two folds, namely from the bank to customers and from the customers to the bank. Clearly, this a disguised riba. In respect to the fiduciary security (dhaman), there is no difference between the both countries. The reasons for the adoption of the security is for the sake of prudentiality in financing disbursed to the customers.Keywords: Akad, Murabahah, Ba’i al-Inah, Dhaman